Awareness and implementation of infection control measures in private dental clinics, Holy Makkah, Saudi Arabia - Mandourh, Mawadah S.; Alhomaidhi, Noura R.; Fatani, Nuha H.; Alsharif, Amjad S.; Ujaimi, Ghufran K.; Khan, Ghaida'a M.; Afifi, Ibtesam Kamel (International Journal of Infection Control, 2017)
Since the majority of dental patients in Holly Makkah are treated in private sector, the aim of the present study was to evaluate attitude and knowledge towards infection control (IC) measures among dentists in private clinics in our region. A self-constructed questionnaire, consisted of 30 items related to IC practices and knowledge, was distributed among 107 private clinics dentists in ten districts of Holly Makkah. The data collected were related to gender, qualification, daily work load and years of experience of the participants. Although significant percentage (P <0.05) of participants had hepatitis B vaccination; 14.9% of them were none vaccinated. A wrong attitude of bending needle after use is common (70%) which is higher by general practitioners (GP), 12.2 % do not dispose sharps in safety box and 2.8% not considering separation of blood socked wastes is important. The wrong knowledge that wearing gloves could replace hand hygiene was reported in 15.9%. All participants were aware that used instruments should be autoclaved, but 4.6% was not realizing the importance of the use of new hand piece for every patient. Higher percentages of dentists with 10 years of experience were none vaccinated; do not perform hand hygiene after removing gloves and unfortunately, they did not receive any educational IC course. In conclusion, the IC practice and knowledge of dentists in Holly Makkah private clinics are below standard levels. So, continued medical education and obligatory training IC programs are recommended for improving their practice and update their knowledge.